The administrative problems of public elementary school administrators in the third congressional district of Cebu for the year 1976-1977 - Mendiola, Carolina 1935- (1977)
This study endeavored to investigate the administrative problems of public elementary school administrators in the Third Congressional District of Cebu for the school year 1976-1977. The descriptive survey method was utilized. The data were collected from 74 respondents by means of a checklist and data sheet. The following are considered problems: provision of lunch counter and utensils, availability of first aid medicine, provision of regular health physical examination, dental and clinical services, provision for guidance servies, such as remedial, regular attendance of pupils, discipline of children, provision for counseling and teachers' holding power, etc.
Includes tables
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: School administrators -- Philippines -- Cebu; Public schools -- Philippines -- Cebu; School management and organization -- Philippines -- Cebu